PENGARUH PARTISIPASI PENYUSUNAN APBD TERHADAP KINERJA APARATUR PEMERINTAHAN DAERAH, MELALUI: KOMITMEN ORGANISASI DAN JRI SEBAGAI VARIABEL MODERATING PADA PEMKO LHOKSEUMWE - Hazmi, Yusri (Jurnal Akuntansi (Media Riset Akuntansi & Keuangan), 2014)
The purpose of this study is to investigate and analyze the effect of budgetaryparticipation on performance of local government officials, organizationalcommitment, and job relevance of information as a moderating variable.This studyuses multiple linear regression to determine the relationship between the dependentvariable of the first 3 independent variables. The sample using purposive samplingmethod. The data were then processed using SPSS version 16.The result showedthat budgetary participation and organizational commitment did not significantlyaffect the performance of the apparatus. From the results of regression testingobtained with the participation value of 0.274 or greater than 0.05. Likewise with theorganizational commitment level of 0.047 siqnifikan and also greater than 0.05.However, unlike the case with JRI, the test results obtained, with siqnifikan level of0.066 or less than 0.05.From the test results of T-test showed a negativerelationship with participation in the performance of the apparatus, and unlike thecase with the commitment of organizations that have a positive relationship. Itmeans that with a high commitment to encourage the performance of officialsPemko Lhokseumawe.Keywords:Participation budget, personnel performance,commitment and job relevant information